Micrometeorology - Foken, Thomas 1949-; Mauder, Matthias 1977- (Springer Atmospheric Sciences, 2024)
Chapter 1: General Basics -- Chapter 2: Basic Equations of Atmospheric Turbulence -- Chapter 3: Specifics of the Near-Surface Turbulence -- Chapter 4: Experimental Methods for Estimating the Fluxes of Energy and Matter -- Chapter 5: Modelling of the Energy and Matter Exchange -- Chapter 6: Measurement Technique -- Chapter 7: Microclimatology -- Chapter 8: Applied Meteorology. .